The myth of more social inclusion through activation reforms: The case of Germany - Sigrid Betzelt (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2015)
The paper presents new findings on a specific 'gendered' problem resulting from 'activation policies' and a certain group of unemployed which has been widely neglected so far in public and academic discourse although it is both quantitatively significant and reveals systematic failures of activation strategies: In contrast with claims of greater social inclusion through 'activation, it can be seen that currently nearly a quarter of a million people in Germany are registered as unemployed without any entitlement to unemployment benefits or any individual social protection like health care. These 'unemployed non-beneficiaries' (UNB), currently account for a quarter of those registered as unemployed within the statutes of the German Social Code Book III (SGB III). Their situation is problematic for two reasons: First, their significant number is evidence of a severe social security gap which has existed before the 'Hartz reforms' but has grown more acute by the new, stricter eligibility rules to unemployment benefits introduced with the reforms. This re-familisation of social security stands in contrast to the more precarious employment structures on the labour market on the one hand, and the more egalitarian gender norms of an individualised society on the other. Second, our recent research findings show that unemployed non-beneficiaries are practically even excluded from active employment promotion services of the Federal Employment Agency (Bundesagentur für Arbeit, BA), despite the fact that they have the same obligations to prove active job search and mostly are not able to find jobs by themselves. The German activation regime even systematically pushes them to de-register as unemployed (to 'improve' the labour market statistics). The paper argues that this can be explained by the business management principles of cost-efficiency introduced with the 'Hartz reforms' as the primary guideline for the Federal Employment Agency. Performance measurement tools which prioritize short-term job insertion and the cost-efficient allocation of the BA-budgets to the more 'marketable' groups of unemployed override social, labour market and political equality targets. This is detrimental for vulnerable groups like unemployed non-beneficiaries, and also contrary to the macro-economic goal of counteracting the reputed skill shortages. The paper is based both on secondary analyses of official statistics and own empirical panel data (GSOEP) and some qualitative findings, derived from own research projects funded by different sources.
Keywords: 330; labour market reforms; activation; managerialism; gender equality; social security; unemployment